2012
DOI: 10.2136/sssaj2012.0055
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term No‐Till Impacts on Organic Carbon and Properties of Two Contrasting Soils and Corn Yields in Ohio

Abstract: Tillage influence on soil properties and crop productivity depends on soil, crop, climate, and duration. Two long-term experimental sites with contrasting soils were selected to assess the influence of no-till (NT), minimum tillage (MT), and plow tillage (PT) under continuous corn (Zea mays L.) and cornsoybean [Glycine max (L.) Merr.] (CS) rotations on soil organic C (SOC) stock, bulk density (p,,), water-stable aggregation (WSA), aggregate tensile strength, penetration resistance, available water capacity (AW… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
86
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 137 publications
(95 citation statements)
references
References 59 publications
4
86
2
Order By: Relevance
“…Tillage affected both SOM and TCs levels, with higher values under tilled plots as opposed to NT. Several studies have reported opposite results, showing increased SOM and TCs under longterm NT compared to tillage practices (West and Post, 2002;Kumar et al, 2012), even under Illinois conditions Zuber et al, 2015). Yet all these later studies reported results from experimental plots with more than 5 yr since treatment establishment whereas the current study has been in place for 3 yr and one complete production cycle in each field.…”
Section: Resultsmentioning
confidence: 56%
“…Tillage affected both SOM and TCs levels, with higher values under tilled plots as opposed to NT. Several studies have reported opposite results, showing increased SOM and TCs under longterm NT compared to tillage practices (West and Post, 2002;Kumar et al, 2012), even under Illinois conditions Zuber et al, 2015). Yet all these later studies reported results from experimental plots with more than 5 yr since treatment establishment whereas the current study has been in place for 3 yr and one complete production cycle in each field.…”
Section: Resultsmentioning
confidence: 56%
“…Soils were slightly acidic with pH varying from 5.03 to 5.70. The calcium carbonate (CaCO 3 ) content of samples was about 0.1%; therefore, soil inorganic C was ignored and total C was considered as the SOC (Kumar et al 2012 ). Climate Data.…”
Section: Soil Physical and Chemical Propertiesmentioning
confidence: 99%
“…This may be true. However, there is a growing body of scientific literature related to the contribution of agronomic best management practices to sequester SOC (Huggins et al 2007;Luo et al 2010;Kumar et al 2012, Lyons et al 1997Janzen 2006;BlancoCanqui and Lal 2008;Casta Junior et al 2013) that suggests that the SOC sequestration rates in table 1 may be too high. Other researchers (Olson 2010;Baker et al 2007;Sanderman and Baldock 2010;Sanford et al 2012) found that SOC stocks declined from pretreatment levels even with long-term NT studies under soilspecific conditions, such as conversion of prairie to agricultural land, drainage, aeration, tillage, and erosion.…”
mentioning
confidence: 99%